(untitled) (Eurasian Journal of Ecology, 2022)
The species diversity of cyanobacteria of Lake Tuzkol, located on the left bank of the upper reaches of the Charyn River in the Rayymbek district in the south-east of the Almaty region, was studied. Microbial biodiversity represents the largest untapped reservoir for the potential discovery of new promising species of microorganisms. The aim of the study was to study the species diversity of Lake Tuzkol and identify promising cyanobacteria species. According to the results of the study of cyanobacteria (Cyanobacteria), 12 species were found in plankton, 15 species in periphyton. The ecological characteristics of cyanobacteria in relation to halobacteria indicate the salinity of the lake under study, there is a predominance of halophilic species. In addition, it was revealed that there are cyanobacteria species in the lake that are indifferent to the salinity of the environment. Indicators of saprobicity were 70% of cyanobacteria. The assessment of the state of the lake water by indicator species of phytoplankton showed that it belongs to the category of oligo-betamezosaprobnaya. The saprobic index according to the Pantle and Bukka method is 1.4. According to the results of work on the isolation of pure cultures from samples taken from the Tuzkol lake, 2 algologically pure cyanobacteria cultures were obtained:. The isolated cultures of cyanobacteria showed high productivity in the nutrient medium BG -11, at a temperature of 30-320C and a light intensity of 6000 lux. Keywords: species composition, biodiversity, cyanobacteria, Lake Tuzkol, saprobicity, algologically pure cultures.